Macular cystoid spaces in patients with retinal dystrophy. (1st October 2016) - Lingao, Michelle D.; Ganesh, Anuradha; Karthikeyan, Arcot S.; Al Zuhaibi, Sana; Al-Hosni, Amna; Al Khayat, Aisha; Capasso, Jenina; Trumler, Anya A.; Stroh, Eliza; Al Shekaili, Hilal; Cater, Jacqueline R.; Levin, Alex V.
ABSTRACT: Background : Non leaking macular cystoid spaces (MCS) are seen in some retinal dystrophies. Carbonic anhydrase inhibitor (CAI) treatment may reduce the size of MSC and improve vision. Methods : A retrospective study of patients with retinal dystrophy with MCS seen between 2009 and 2013 at two sites. Patients had ophthalmic examination, optical coherence tomography (OCT) and genetic testing. Patients with vision worse than 20/30 were treated with CAI. Post treatment visual acuity (VA), central foveal zone (CFZ) thickness, and qualitative estimation of MCS size were assessed. Results : Eighteen patients, 6–47 years old, were included. IVFA was performed in 15 (83%) patients. Of the 26 eyes in 13 patients who were treated and followed, VA improved in 15 eyes (58%) of 10 patients. Ten of these 15 eyes had decreased CFZ thickness and 9/10 showed qualitative MCS improvement. Regression analysis showed that change in CFZ thickness was not significantly predictive of change in final visual acuity (p = 0.405). Five of 15 eyes with improved VA had paradoxically increased CFZ thickness and 2/5 had enlarged MCS. Three of the treated eyes (11%) in two patients had decreased VA with decreased CFZ thickness and improved MCS in 2/3 eyes. Eight eyes (31%) in six patients showed no change in VA with decreased CFZ thickness in 6/8 eyes with improved MCS. Genetic testing showed mutations of NR2E3, XLRS, CRB1, GPR98 and CNGB1. Conclusion : Non-leaking MCS occur in a variety of retinal dystrophies. Therapy with topical or systemic CAI has variable efficacy and may result in VA improvement with or without qualitative improvement in MCS and CFZ thickness.